Yogurt consumption and risk of accelerated aging: A population-based study from the NHANES 2003–2006 - Yue, Xinghai; Liu, Hongfei; Guo, Wenzhao; Gao, Yuhang; Shi, Shaoshun (Frontiers in Nutrition, 2024)
Yogurt consumption is beneficial to health, but its association with aging remains unclear. We used data from the 2003-2006 National Health and Nutrition Examination Survey (NHANES) (n=4056) to explore the relationship between yogurt consumption and aging. Yogurt consumers were defined as individuals who consumed yogurt more than once per yearat least once per year. Phenotypic age acceleration was used as a surrogate marker for aging. After nearest-neighbor propensity score matching (PSM), we conducted weighted multivariate logistic regression analysis, subgroup analysis, and restricted cubic spline (RCS) to explore the relationship between yogurt consumption and aging. The results showed that yogurt consumption was associated with a lower risk of accelerated aging compared to non-consumers (OR (95%) = 0.544 (0.354 -0.836), P = 0.020), with a U-shaped relationship observed between the frequency of yogurt intake and the risk of accelerated aging. Additionally, we found that yogurt consumption was related to a lower risk of overweight status. These findings may provide a promising avenue for exploring the beneficial effects of dietary factors on extending lifespan.